2020
DOI: 10.1093/mnras/staa1576
|View full text |Cite
|
Sign up to set email alerts
|

Systematic opacity calculations for kilonovae

Abstract: Coalescence of neutron stars (NSs) gives rise to kilonova, thermal emission powered by radioactive decays of freshly synthesized r-process nuclei. Although observational properties are largely affected by bound–bound opacities of r-process elements, available atomic data have been limited. In this paper, we study element-to-element variation of the opacities in the ejecta of NS mergers by performing systematic atomic structure calculations of r-process elements for the first time. We show that the distribution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
296
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(312 citation statements)
references
References 83 publications
13
296
3
Order By: Relevance
“…Fernández & Metzger 2013;Just et al 2015). This justifies our choice of κ w = 5 cm 2 g −1 , which is appropriate for outflows with intermediate Y e ∼ 0.25 -0.35 (Tanaka et al 2020).…”
Section: Constraints On the Ejecta And On The Binary Propertiesmentioning
confidence: 60%
See 1 more Smart Citation
“…Fernández & Metzger 2013;Just et al 2015). This justifies our choice of κ w = 5 cm 2 g −1 , which is appropriate for outflows with intermediate Y e ∼ 0.25 -0.35 (Tanaka et al 2020).…”
Section: Constraints On the Ejecta And On The Binary Propertiesmentioning
confidence: 60%
“…As a further simplification, we fix the average (root mean square) velocity v and the (grey) opacity κ of the remaining two components to plausible values, namely v t = 0.3c and κ t = 15 cm 2 g −1 for the tidal ejecta and v w = 0.1c and κ w = 5 cm 2 g −1 for the viscous disc wind, based on their expected velocity and composition: the tidal ejecta are typically expected to retain a very low electron frac- tion Y e < 0.2 (e.g. Fernández et al 2017) leading to efficient r-process nucleosynthesis of Lanthanides and hence a high opacity κ t > 10 cm 2 g −1 (Tanaka et al 2020); disc wind outflows feature a wider range of Y e , due to viscous heating and neutrino irradiation from the inner part of the disc. Differently from NS-NS mergers, though, the absence of shocks and of intense neutrino production by a meta-stable neutron star remnant are likely to cause the disc wind to remain significantly neutron-rich (e.g.…”
Section: Constraints On the Ejecta And On The Binary Propertiesmentioning
confidence: 99%
“…Theoretical modeling of NSM r-process suggests that both the lighter and heavier r-process elements could be produced in the early dynamical ejecta and/or the later wind outflow from the remnant [225,243,244]. However, recent careful re-analysis of the spectra [245] and many other related studies (e.g., [246,247]) have indicated that the amount of lanthanoids is not as large as that expected in theoretical calculation for kilonova associated with GW170817. Meanwhile, the detection of the infrared emission at several tens of days has not yet been able to provide evidence for the presence of 254 Cf or αdecay nuclei.…”
Section: Highlights From Astronomical Observations and Theoretical Progressmentioning
confidence: 88%
“…While these effects can be controlled and deconvolved with the aid of a radiation transport model as it has been done for supernovae of all types (Mazzali et al, 2016;Hoeflich et al, 2017;Ergon et al, 2018;Hillier and Dessart, 2019;Ashall and Mazzali, 2020;Shingles et al, 2020), a more fundamental hurdle in modeling kilonova spectra consists in the much larger number of electronic transitions occurring in r-process element atoms than in the lighter ones that populate supernova ejecta, and in our extremely limited knowledge of individual atomic opacities of these neutron-rich elements, owing to the lack of suitable atomic data. First systematic atomic structure calculations for lanthanides and for all r-process elements were presented by Fontes et al (2020) and Tanaka et al (2020), respectively.…”
Section: Kilonova Light Curve and Spectrummentioning
confidence: 99%